ANCAMAN BAGI PELAKU ZHALIM PERSPEKTIF QURAISH SHIHAB ANALISIS Q.S AL-BURUJ AYAT 10 - Ardiansyah, Muhammad Soffin; Yeti Dahliana (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study examines the threats faced by perpetrators of injustice from the perspective of the Qur’an, focusing on an analysis of Qur’anic Surah Al-Burūj, verse 10, through the interpretation of Muhammad Quraish Shihab. Injustice is one of the fundamental issues in the teachings of the Qur’an because it has far-reaching implications for human moral, social, and spiritual life. This study aims to examine the meaning of injustice, the forms of divine threats against perpetrators of injustice, and the moral message contained in the verse. The research method employed is library research using a qualitative approach and thematic analysis (tafsir maudhū‘ī). The primary sources of this study are the Qur’an and Muhammad Quraish Shihab’s Tafsir al-Mishbah, which were analyzed using content analysis techniques. The results of the study indicate that oppression in Surah Al-Buruj, verse 10, does not only refer to acts of physical oppression against the faithful but also encompasses various forms of injustice that undermine human dignity and violate the principles of divine justice. The threat of the torment of Hell and the burning torment in this verse affirms the certainty of Allah’s retribution against the perpetrators of oppression. From Quraish Shihab’s perspective, oppression is understood as the act of placing something where it does not belong, which leads to the corruption of moral, social, and spiritual order. Therefore, this verse serves as both a theological warning and moral instruction for humanity to avoid oppression. From Quraish Shihab’s perspective, injustice is understood as the act of placing something where it does not belong, which leads to the breakdown of moral, social, and spiritual order. Therefore, this verse serves as both a theological warning and a moral lesson, urging people to avoid injustice and uphold justice in their lives.